2012
DOI: 10.1021/pr300318m
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fate of Tea Polyphenols in Humans

Abstract: Polyphenols, a ubiquitous group of secondary plant metabolites sharing at least one aromatic ring structure with one or more hydroxyl groups, represent a large group of natural antioxidants abundant in fruits, vegetables, and beverages, such as grape juice, wine, and tea, and are widely considered to contribute to health benefits in humans. However, little is yet known concerning their bioactive forms in vivo and the mechanisms by which they may alter our metabolome, which ultimately contribute toward disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…To overcome the limitations of targeted data-mining techniques, a few untargeted analysis methods, including metabolomics (Xie et al, 2012;Yan et al, 2013) and in-house-developed background subtraction techniques (Gong et al, 2012;Yan et al, 2013), have been applied to the detection of TCM components in vivo. In this study, PATBS has demonstrated several distinct advantages over targeted and other untargeted LC/MS approaches in detecting TCM components in complex biologic samples.…”
Section: Downloaded Frommentioning
confidence: 99%
“…To overcome the limitations of targeted data-mining techniques, a few untargeted analysis methods, including metabolomics (Xie et al, 2012;Yan et al, 2013) and in-house-developed background subtraction techniques (Gong et al, 2012;Yan et al, 2013), have been applied to the detection of TCM components in vivo. In this study, PATBS has demonstrated several distinct advantages over targeted and other untargeted LC/MS approaches in detecting TCM components in complex biologic samples.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The treated group was orally fed 0.4 mg.g -1 of CHT daily for 38 days, while control rats received the same amount of water. Urine samples were collected at days 0, 8,14,20,26,33 and 38 during the Herbal Tea treatment period. Precipitated solids were removed by centrifugation at 12,000 rpm, and urine samples were stored at -80°C prior to GC-MS analysis.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…In comparison of genomics and proteomics, metabonomics enables the monitoring of real end-point metabolic changes following physiological and pathophysiological stimuli [13] and interpret holistic, quantitative data on time-dependent metabolic variation in response to a xenobiotic intervention, without prior knowledge of its composition. Recently, considerable efforts are being expended to enhance the understanding of the mechanisms of and individual responses to dietary intervention with the aid of metabonomics [14][15][16]. However, current studies are still relatively simple because the active ingredients have known biochemical targets.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols describes the chemical compound structure of having several hydroxyl functional groups (−OH) attached to an aromatic hydrocarbon group (Xie et al, 2012). Categorized as secondary metabolites, polyphenols can also be divided into smaller subgroups.…”
Section: Catechinsmentioning
confidence: 99%